2007
DOI: 10.2106/jbjs.e.01396
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stem Cells Influence Early Tendon-Healing in a Rabbit Achilles Tendon Model

Abstract: Intratendinous cell therapy with bone marrow-derived mesenchymal stem cells following primary tendon repair can improve histological and biomechanical parameters in the early stages of tendon-healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
185
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(197 citation statements)
references
References 25 publications
9
185
2
1
Order By: Relevance
“…2,8,27,61 BMSCs contracted onto pretensioned suture resulted in greater loadrelated structural and material properties when used to repair Achilles tendon defects. 61 Similar improvements were seen when a BMSC-collagen mixture was implanted into surgically created patellar tendon defects.…”
Section: Stem Cell Augmentation Of Tendon Healing and Rc Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…2,8,27,61 BMSCs contracted onto pretensioned suture resulted in greater loadrelated structural and material properties when used to repair Achilles tendon defects. 61 Similar improvements were seen when a BMSC-collagen mixture was implanted into surgically created patellar tendon defects.…”
Section: Stem Cell Augmentation Of Tendon Healing and Rc Repairmentioning
confidence: 99%
“…The authors conclude that improvements in primary tendon repair with intratendinous cell therapy are restricted to the early stages of tendon healing. 8 Two different studies recently used a rat Achilles tendon model to compare MSC therapy versus other cell therapy, with important results. In one report, the Achilles was transected, including the enthesis, before surgical repair without cell injection, with chondrocyte injection, or with MSC injection.…”
Section: Stem Cell Augmentation Of Tendon Healing and Rc Repairmentioning
confidence: 99%
“…A wide range of donor cell types have been used to promote tendon healing in pre-clinical studies, including bone marrow-derived mesenchymal stem cells (BMSCs) [3,4,5], periodontal ligament or gingival tissue [6], dermal fibroblast [7], tenocytes [8], peripheral blood-derived MSCs [9,10] and embryonic stem cell derived MSCs (ESC-MSCs) [11]. Each cell source has its limitations including inferior proliferation, differentiation and collagen production abilities of tenocytes [12,13,14,15], risk of teratoma formation of ESCs as well as risk of ectopic bone [3] and tumor induction [16] of BMSCs when using a certain scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental laboratory studies on animal models using MSCs embedded on various types of scaffolds have returned some encouraging but inhomogenous results. Chong et al 40 used MSCs with fibrin sealant in a rabbit Achilles tendon model. In their study, no differences between fibrin and fibrin with MSC could be shown histologically.…”
Section: Resultsmentioning
confidence: 99%